Bidirectional ultrahigh-repetition-rate ultrafast fiber laser. (October 2021) - Jiang, Jia-Min; Chen, Xuan-Juan; Gao, Yu-Xin; Liu, Meng; Bai, Zhen-Ao; Luo, Ai-Ping; Xu, Wen-Cheng; Luo, Zhi-Chao
Highlights: The DFWM mode-locked fiber laser with a bidirectional main cavity was demonstrated. The 100 GHz and 30 GHz pulses were obtained in clockwise and counter-clockwise directions. The single-waveband tunable and dual-waveband switchable operations could be achieved. Abstract: We proposed a bidirectional high-repetition-rate (HRR) ultrafast fiber ring laser based on the dissipative four-wave-mixing (DFWM) mode-locked technique. By employing a segment of highly nonlinear fiber (HNLF) and two comb filters with different free spectral ranges (FSRs), 100 GHz and 30 GHz HRR pulses were obtained in the clockwise (CW) and counter-clockwise (CCW) directions, respectively. Moreover, the single-waveband tunable and dual-waveband switchable operations of the HRR pulse could be achieved for each direction. The flexible and compact bidirectional HRR ultrafast fiber laser would find potential applications in the related fields such as optical communications and sensing.